Simon of Genoa's Medical Lexicon - Zipser, Barbara (De Gruyter, 2013)
"Simon of Genoa's Medical Lexicon", an edited volume based on the conference held on March 17th, 2012, is part of the Simon Online project - a dynamically growing Wiki edition of Simon of Genoa's Clavis sanationis, a Latin-Greek-Arabic medical dictionary from the late 13th century. In the individual articles, written by well-known scholars, authorities in their fields of research, Simon and his major work, are approached from different perspectives and as a whole. The volume offers a comprehensible and well-balanced collection of current research on Simon and Clavis sanationis. The volume demonstrates the importance of the Clavis, not only for the history of pharmacology and medicine, but also for Byzantine and medieval studies, Roman, Greek, Latin and Arabic philology and lexicography. Barbara Zipser (Doctor of Philosophy, Wellcome Trust University Award 2006, 2010) is a researcher at the Centre for the Study of the Body and Material Culture, History Department, Royal Holloway University of London. Her main field of research is Greek medicine from Galen to the late Middle Ages, with an emphasis on textual criticism, manuscript transmission, and the formation of Greek vernacular terminology. Dr Zipser is a well-known and promising young scholar in the field of Ancient and Medieval Medicine. She runs Simon Online (http://www.simonofgenoa.org) - the joint edition and translation project of Simon of Genoa's Clavis sanationis, a dictionary of Latin, Greek and Arabic medical terminology in Wiki format.